BUILDING SCIENCE AND CHARACTER EDUCATION AS A FORM OF QUALITY EDUCATION AT STATE ELEMENTARY SCHOOL 067099 IN MEDAN - Roma Sri Rezeki Sitorus; Claudia Canniagi Br. Simanihuruk; Agustina Sinambela; Dya Komala Br. Munthe; Jesika; Juan Alexander Sitepu; Muhammad Ridwan; Nur Kholisy Geovani (RADJA PUBLIKA, 2024)
Literacy and numeracy are skills that everyone must have to survive and contribute to the civilization of the nation. In addition, education must also be owned by everyone to develop life according to the civilization of the times. Literacy, numeracy and education are important issues globally and in Indonesia because it is predicted that there are still many people out of school, lacking basic literacy and numeracy skills, and there are still few countries that reach the target number of citizens who successfully complete the high school education level by 2030. This is also confirmed by Indonesia's literacy and numeracy PISA score in 2022 which decreased when compared to Indonesia's literacy and numeracy PISA score in 2018 and the finding that many students of SDN 067099 are still not fluent in reading and arithmetic. Therefore, the writing group took the initiative to carry out community service activities in the form of a teaching campus. There are 2 methods applied in this activity, namely the Game Method and the Leathuring Method. The service activities were carried out in 4 stages, namely preparation for activities, first day teaching activities, second day teaching activities, and closing. On the first day we taught grade 1 and 2 elementary school students. While on the second day, we taught students in grades 3 and 4. After the service activity, students' literacy, numeracy, and moral skills have improved and are getting better.